Factors Associated With The Incidence Of Type II Diabetes Mellitus Among Elderly In Coastal Area Of Lingkar Timur Public Health Center, Bengkulu City - Maya Diana Agustina; Tuti Rohani; Wulandari Wulandari (Student Scientific Journal, 2026)
Background: Type II diabetes mellitus (T2DM) is a chronic metabolic disorder characterized by high blood glucose due to insulin resistance. The elderly are at high risk because of physiological decline and limited physical activity. Objective: To determine factors associated with the incidence of T2DM among elderly in the coastal area of Lingkar Timur Public Health Center, Bengkulu City. Methods: This was a quantitative study with a cross-sectional design involving 93 respondents selected using simple random sampling. Data were collected via questionnaire and analyzed using Chi-Square test at 95% confidence level. Results: Most respondents had poor knowledge (65.6%), family history of DM (69.9%), adequate physical activity (64.5%), and T2DM incidence (67.7%). There were significant relationships between knowledge (p=0.001), family history (p=0.001), and physical activity (p=0.002) with T2DM incidence. Conclusion: Knowledge, family history, and physical activity are significantly associated with T2DM among elderly.